Effect of acupressure applied after cesarean section under spinal anesthesia postpone the duration of taking analgesics and on the gastrointestinal system: A randomized controlled trial - Şolt Kırca, Ayça; Kanza Gül, Derya (Elsevier Science Inc, 2023)
Objectives: Cesarean deliveries are one of the primary conditions associated with postoperative decreased motility of the gastrointestinal system and are characterized by acute pain and distention. The aim of the present study was to investigate the application of acupressure and the administration of analgesics for women who underwent cesarean section under spinal anesthesia could be delayed and how spontaneous gastrointestinal system motility could be achieved in the postoperative period.Design: Randomized controlled trialSetting: Private Medipol Nisa Hospital, Istanbul, Turkey Intervention: This trial was conducted with 112 primipara pregnant women who delivered via cesarean sec-tion under spinal anesthesia and were randomly assigned into the acupressure (n=52) and control (n=60) groups. The participants in the acupressure group (n=52) were treated for 20 minutes. The participants in the control group (n=60) were treated per the hospital protocol (analgesics for pain, flatulation and defecation, no pharmacological or non-pharmacological application was performed).Results: The time that elapsed for the administration of analgesics was significantly later in the acupressure group than in the control group (p <.001). The first occurrence of flatulation and defecation were signifi-cantly earlier in the acupressure group (19 and 23 hours, respectively) than in the control group (34 and 27 hours, respectively) (p <.001).Conclusion: Acupressure is an easy, non-invasive method that postpones the administration of analgesics in the postoperative period and prevents flatulence and constipation caused by the decreased motility of GIS.
Keywords: Acupressure; Cesarean Section; Gastrointestinal Motility; Postoperative Period; Postpones Taking Analgesics